2009
DOI: 10.1016/j.jpeds.2008.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in Pediatric Osteosarcoma: Response and Toxicity in Relation to Genetic Polymorphisms and Dihydrofolate Reductase and Reduced Folate Carrier 1 Expression

Abstract: ObjectiveTo determine the influence of the genotype and the level of expression of different enzymes involved in folate metabolism on the response to and toxicity of high-dose methotrexate treatment in pediatric osteosarcomas. Study designDHFR and Reduced folate carrier 1 (RFC1) semiquantitative expression was analyzed in 34 primary and metastatic osteosarcoma tissues by real-time polymerase chain reaction. The following polymorphisms were also analyzed in peripheral blood from 96 children with osteosarcoma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…Thus, it mainly prevents de novo pyrimidine and purine syntheses (Celtikci et al, 2009;Patiño-García et al, 2009;Shimura et al, 2009). It has been reported that MTX efficiently suppresses PIA when given after the onset of arthritis, but the mechanism remains obscure (Lange et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it mainly prevents de novo pyrimidine and purine syntheses (Celtikci et al, 2009;Patiño-García et al, 2009;Shimura et al, 2009). It has been reported that MTX efficiently suppresses PIA when given after the onset of arthritis, but the mechanism remains obscure (Lange et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric osteosarcomas, it was proposed that impaired intracellular transport of MTX by decreased RFC levels is the most feasible mechanism of acquired resistance (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6,[13][14][15][16] In osteosarcoma, MTHFR c.677C>T p.Ala 222 Val increased hematological toxicity but did not influence survival. 17 Cisplatin and doxorubicin form helix-distorting DNA adducts resulting in strand breakage and inhibition of replication. Restoration of damaged DNA is by nucleotide excision repair (NER), whereas glutathione-S-transferase (GST) enzymes play a detoxification role.…”
Section: Introductionmentioning
confidence: 99%